Usefulness of a laser-cut covered metal stent with a 7F delivery sheath in endoscopic ultrasound-guided biliary drainage without fistula dilation - Takeshita, Kotaro; Hijioka, Susumu; Nagashio, Yoshikuni; Maruki, Yuta; Ohba, Akihiro; Kawasaki, Yuki; Hisada, Yuya; Yoshinari, Motohiro; Harai, Shota; Kitamura, Hidetoshi; Koga, Takehiko; Maehara, Kosuke; Murashima, Yumi; Yamada, Natsumi; Okada, Mao; Takasaki, Tetsuro; Agarie, Daiki; Hara, Hidenobu; Hagiwara, Yuya; Okamoto, Kohei; Yamashige, Daiki; Kondo, Shunsuke; Morizane, Chigusa; Ueno, Hideki; Saito, Yutaka; Okusaka, Takuji (Endoscopy International Open, 2023)
Background and study aims Recently, the utility of endoscopic ultrasound-guided intervention without fistula dilation (EUS-IV WoD) has been reported to prevent adverse events. We clinically evaluated cases in which EUS-IV WoD was attempted using a novel self-expandable metallic stent (SEMS); this is a fully covered, laser-cut SEMS that has a tapered and stiff tip specifically designed for a 0.025-inch guidewire and a relatively thin, 7F delivery system.Patients and methods We retrospectively evaluated cases wherein EUS-IV WoD was attempted using the novel SEMS between March and December 2021.Results Treatment of 11 patients by EUS-IV WoD with the novel SEMS was attempted. The technical success rate for EUS-IV was 100 % and the clinical success rate was 100 %; the success rate for EUS-IV WoD was 72.8 %. Of these, the procedural success rate for EUS-IV WoD was 100 % in EUS-biliary drainage (BD) and 57.1 % in non-EUS-BD. Early adverse events were observed in 27.3 % of patients (3/11): mild abdominal pain in two patients and moderate bleeding in one patient. The abdominal pain cases were both cases of EUS-IV WoD failure and required fistula dilation. Conclusions The novel stent may be useful for EUS-IV WoD, especially in EUS-BD.